1988
DOI: 10.1017/s0305004100065221
|View full text |Cite
|
Sign up to set email alerts
|

Filtrations, closure operations and prime divisors

Abstract: Let ƒ = {In}n ≽ 0 be a filtration on a ring R, let(In)w = {x ε R; x satisfies an equation xk + i1xk − 1 + … + ik = 0, where ij ε Inj} be the weak integral closure of In and let ƒw = {(In)w}n ≽ 0. Then it is shown that ƒ ↦ ƒw is a closure operation on the set of all filtrations ƒ of R, and if R is Noetherian, then ƒw is a semi-prime operation that satisfies the cancellation law: if ƒh ≤ (gh)w and Rad (ƒ) ⊆ Rad (h), then ƒw ≤ gw. These results are then used to show that if R and ƒ are Noetherian, then the sets A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In [7] result 2.3.2 and Theorem 2.6 (Cancellation law), the authors misquoted what Rees has shown in pages 11-12 of his paper entitled: Asymptotic properties of ideals, preprint. Indeed they did not require the nitrations / and g to be noetherian.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In [7] result 2.3.2 and Theorem 2.6 (Cancellation law), the authors misquoted what Rees has shown in pages 11-12 of his paper entitled: Asymptotic properties of ideals, preprint. Indeed they did not require the nitrations / and g to be noetherian.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed they did not require the nitrations / and g to be noetherian. Our paper originated with the attempt to show that Theorem 2.6 (Cancellation law) of [7] holds for arbitrary nitrations / and g provided that the filtration h be strongly AP. In addition we show here that this Cancellation law does not hold for arbitrary h even if h is AP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, reductions of modules were introduced and developed in [16], and their "dual" concept was investigated in [20]. Also, there have been several recent papers in which a number of important theorems for ideals in Noetherian rings have been extended to Noetherian filtrations (for example, see [1, 8,9,14,15,18]). (Filtrations are generalizations of the sequence of powers of a given ideal, and there are many important filtrations (such as the sequence {q^} n >Q of symbolic powers of a primary ideal q and the sequence { (I n ) a } n >o of integral closures of the powers of an ideal /) which are generally not powers of an ideal, but which are quite often Noetherian filtrations.…”
Section: Introduction Reductions Of Ideals Were Introduced In [6]mentioning
confidence: 99%